(untitled) (International journal of artificial intelligence, 2025)
The Programme for International Student Assessment (PISA) provides a valuable framework for evaluating and improving science education. While primarily designed for 15-year-olds, its principles can enhance primary school science instruction by promoting inquiry-based learning, critical thinking, and real-world problem-solving. Integrating PISA’s methodologies helps develop scientific literacy, encourages hands-on exploration, and aligns teaching practices with global educational standards. This paper explores how PISA’s approach can be adapted to primary education, addressing benefits, challenges, and the role of technology in fostering scientific understanding. By aligning early science education with PISA principles, students gain essential skills for future academic and real-life applications.